Limits of Islamism Jamaat-e-Islami in contemporary India and Bangladesh - Islam, Maidul (Cambridge University Press, 2015)
The book examines the dynamics from the formation of Islamist politics for the struggle for hegemony to failure to become a hegemonic force in Bangladesh. The contradiction between Islamic universalism/Islamist populism, on one hand, and a politics of Muslim particularism in India, on the other, is revealed in this study.